The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2020
DOI: 10.1002/ange.202004104
|View full text |Cite|
|
Sign up to set email alerts
|

Deep Eutectic Supramolecular Polymers: Bulk Supramolecular Materials

Abstract: Application of new strategies for supramolecular self‐assembly can significantly impact the properties and/or functions of supramolecular polymers. To realize a facial strategy for the development of solvent‐free supramolecular polymers in bulk, “deep eutectic solvents” were employed. Cyclodextrins and natural acids were used to prepare deep eutectic supramolecular polymers (DESPs). Deep eutectic solvents have special characteristics that endow DESPs with unique macroscopic properties and excellent processabil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 78 publications
0
18
0
Order By: Relevance
“…43,45,46 Temperature-induced transitions from mixtures of nonsticky solids to highly viscous soft materials were observed ( Figure 1b and Supporting Information Videos S1 and S2), indicating the occurrence of supramolecular polymerization between the sugars and acids. 9 In constrast, individual acids or sugars were nonviscous and did not show any adhesion effect. Compared with the 1 H NMR spectra of the simply mixed sugars and acids, no changes were observed in the 1 H NMR spectra of deep eutectic supramolecular adhesive materials ( Figure 1b and Supporting Information Figures S2-S13), which demonstrated that no esterification or etherification took place at 60°C.…”
Section: Resultsmentioning
confidence: 92%
See 4 more Smart Citations
“…43,45,46 Temperature-induced transitions from mixtures of nonsticky solids to highly viscous soft materials were observed ( Figure 1b and Supporting Information Videos S1 and S2), indicating the occurrence of supramolecular polymerization between the sugars and acids. 9 In constrast, individual acids or sugars were nonviscous and did not show any adhesion effect. Compared with the 1 H NMR spectra of the simply mixed sugars and acids, no changes were observed in the 1 H NMR spectra of deep eutectic supramolecular adhesive materials ( Figure 1b and Supporting Information Figures S2-S13), which demonstrated that no esterification or etherification took place at 60°C.…”
Section: Resultsmentioning
confidence: 92%
“…4,5 Supramolecular polymer structures and hydrogen bond formation give rise to the cohesive and adhesive properties. [6][7][8][9] However, water can be easily removed from the sugar-water supramolecular polymeric systems during the practical adhesion process, thus leading to a significant attenuation of adhesion strength or adhesion effect. 10,11 With the rapid development of artificial polymeric adhesives in the past century, natural adhesives were no longer the research focus of modern adhesives.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations